1993
DOI: 10.2307/2298060
|View full text |Cite
|
Sign up to set email alerts
|

How Fast do Rational Agents Learn?

Abstract: A simple dynamic model of rational learning through market interaction by asymmetrically informed risk-neutral agents, uncertain about a valuation parameter but whose pooled information reveals it, is presented. The model is a variation of the classical partial equilibrium model of learning in rational expectations in which the market price is informative about the unknown parameter only through the actions of agents. It is found that learning from market prices and convergence to the rational expectations equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(105 citation statements)
references
References 27 publications
(12 reference statements)
6
99
0
Order By: Relevance
“…It avoids the criticism levied against the herding models that their discrete choice space is needed (Lee 1993, Vives 1993) and that market clearing prices interfere with the effect (Avery and Zemsky, 1998). This bubble-like outcome does not rely on agents who are not subject to transversality conditions (as in Blanchard and Watson, 1982), or are otherwise not fully rational.…”
Section: Resultsmentioning
confidence: 99%
“…It avoids the criticism levied against the herding models that their discrete choice space is needed (Lee 1993, Vives 1993) and that market clearing prices interfere with the effect (Avery and Zemsky, 1998). This bubble-like outcome does not rely on agents who are not subject to transversality conditions (as in Blanchard and Watson, 1982), or are otherwise not fully rational.…”
Section: Resultsmentioning
confidence: 99%
“…Our main aims in the paper are to show that this typically creates a bias toward old information, and to study how this bias affects the speed of learning. 1 The baseline model PA (for population average) builds on Vives [19]. A new cohort of agents arrives at each stage (1, 2, ..., n, ... and so on) and must choose an action once and for all in order to minimize a quadratic loss function.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Vives [19] assumes that the full sequence of actions is observed, but that each action is observed with noise, so once again beliefs cannot be perfectly recovered from actions. He shows that the rate of learning slows to n 1 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Grossman (1976), Townsend (1978), and Grossman and Stiglitz (1980) introduce the notion of rational-expectations equilibrium to capture the idea that prices aggregate information that is dispersed in the economy. Wilson (1977), Milgrom (1981), Vives (1993), Pesendorfer and Swinkels (1997), and Reny and Perry (2006) provide strategic foundations for the rational-expectations equilibrium concept. Another strand of literature investigates information aggregation when agents learn only through private interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Vives (1993) showed that when agents learn noisy public information from others, then they learn the truth at a slow speed of t 1/3 (where t is the number of periods of market interactions). The slow convergence result is due to an informational externality.…”
Section: Introductionmentioning
confidence: 99%